RELAÇÃO ENTRE A PERDA DE DENTES APARENTES NO SORRISO COM A QUALIDADE DE VIDA - Miranda Silva, Myllena; Moreira de Moraes, Angelica; Silva da Silva, Rebeca; Claini Bispo Dias, Quêmilli; do Capibaribe Sousa Ferreira, Kendall; Wagmacker Ferreira, Djeyne (Revista Brasileira de Saúde Funcional, 2022)
Insira o resumo aqui